Traces of dispersion: Online media and diasporic identities. Issue 1 (1st March 2014) - Diminescu, Dana; Loveluck, Benjamin
Drawing mainly on the e-Diasporas Atlas project (www.e-diasporas.fr), this article seeks to understand how the web has affected diasporic self-representations. More specifically, by engaging with both media theory and migration studies, it addresses the new modes of boundary formations that arise in the context of migration flows, and how these are mediated by the web. It sheds light on two main levels of online diasporic identity-building. The first can be situated firmly within a paradigm of 'graphic reason', and relates to the socio-semiotic traces documented on diasporic websites. The second examines traces of another kind, which are formed by the hyperlinked networks of e-Diasporas on the web, and which can be situated within a paradigm of 'digital reason'. Some of the consequences for diasporic identity-formation are drawn out, particularly issues relating to strategies of visibility on the web.